Chest wall hernias - Maggiolo, José; Pomi, Jorge; Brandolino, Mario; Bruno, Gerardo; Arévalo, Carlitos (Cirugía del Uruguay, 2006)
This analysis refers the experience of our working group in “Herniation of Thoracic Wall” over a 10-years period. One of the main conclusions is that it is rare though not exotic. It has well defined and typical clinical and anatomopathologic characteristics wich render possible a precise diagnosis.